Box of bones. Book one - Jama-Everett, Ayize, 1974-; Jama-Everett, Ayize, 1974-; Jennings, John, 1970- (Rosarium Publishing, 2021)
"When Black graduate student Lyndsey begins her dissertation work on a mysterious box that pops up during the most violent and troubled time in Africana history, she has no idea that her research will lead her on a phantasmagorical journey from West Philadelphia riots to Haitian slave uprisings. Wherever Lyndsey finds someone who has seen the Box, chaos ensues. Soon, even her own sanity falls into question. In the end, Lyndsey will have to decide if she really wants to see what's inside the Box of Bones. Described as 'Tales from the Crypt meets black history,' Box of Bones is a supernatural nightmare tour through some of the most violent and horrific episodes in the African Diaspora"--